PARADIGM OF ISLAMIC RELIGIOUS EDUCATION TEACHERS AS PROFESSIONAL EDUCATORS - MZ Muttaqien H. Lagala (Adisam Publisher, 2025)
The paradigm of Islamic education, Islamic Religious Education teachers have an important role in shaping the Islamic personality of students. They are also expected to be able to develop knowledge without reducing the values it contains, thus creating a strong education system both materially and spiritually. Thus, the paradigm of Islamic Religious Education teachers as professional educators have moral responsibility, professional abilities, pedagogical competence, and an important role in shaping the Islamic personality of students. Teacher professionalism is crucial because without it, teachers cannot improve the quality of learning. As professional educators, Islamic Religious Education teachers are required to have professional abilities because educating is the main task entrusted to them. They are responsible for shaping the Islamic personality of students. Islamic Religious Education teachers are one of the professional jobs, which starts with a calling, moral, social, and scientific responsibility. They can work not only as teachers but also as researchers guides and motivators who support the spiritual and academic development of students. This ensures that religious education emphasizes more than just theoretical concepts; it also practical applications in everyday life.